Ways to Improve Internal Audit in The Process of Transforming Food Industry Enterprises - Ibragimov Ganijon Gayratovich (European Science Publishing, 2023)
This article describes the scientific-theoretical and methodological basis of transformation of food industry enterprises and the application of internal audit, alternative options for implementation of transformation processes in enterprises are presented, the methodology of applying the "three lines of defense" model in the process of transformation is explained, and food- suggestions on improving the quality of internal audit in food industry enterprises are given.
Keywords: food industry, transformation, transformation of food industry enterprises, audit, internal audit, audit quality, audit organizations, internal audit function, principles of internal audit, ways to improve the quality of internal audit